2019
DOI: 10.1177/1043659619865585
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Nursing Excellence Through Equality: The Relationship Between Magnet® Status and Organizational LGBTQ Client Services and Support

Abstract: Introduction: Human Rights Campaign annually scores health care treatment of lesbian, gay, bisexual, transgender, and queer (LGBTQ) employees and clients among four measured dimensions in its Healthcare Equality Index (HEI). The purpose of this study was to determine if the score organizations earned on the 2018 HEI dimension measuring LGBTQ client services and support correlated with organizations’ American Nurses Credentialing Center Magnet® recognition status, a distinction of nursing excellence. Method: Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Center had higher levels of LGBTQ+-specific client services and support and commitment to LGBTQ + equality. Healthcare organizations with Magnet® status must exhibit policies that indicate implementation of evidence-based care into practice (Blackwell, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Center had higher levels of LGBTQ+-specific client services and support and commitment to LGBTQ + equality. Healthcare organizations with Magnet® status must exhibit policies that indicate implementation of evidence-based care into practice (Blackwell, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Scholarly inquiries have also shown a relationship between organizational nursing quality indicators and organizational commitment to the care of LGBTQ+ individuals. For example, Blackwell (2019) found that healthcare organizations that achieved Magnet® status from the American Nurses Credentialling Center had higher levels of LGBTQ+‐specific client services and support and commitment to LGBTQ+ equality. Healthcare organizations with Magnet® status must exhibit policies that indicate implementation of evidence‐based care into practice (Blackwell, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By looking into what hospitals are doing in terms of training and increasing LGBTQIA+ awareness, you can see how your own institution compares. For example, hospitals with Magnet ® status show a high commitment to providing LGBTQIA+ services and support 8. Emulating programs from Magnet status hospitals can offer a way to standardize LGBTQIA+ care training or provide a foundation if no formal process is in place.…”
Section: Lgbtqia+ Education Isn't Stagnantmentioning
confidence: 99%